An Educational Strategy from a Dentistry Approach to Increase Breastfeeding Knowledge, Attitudes, and Skills (2019)
A strategy from a dentistry perspective, involving educational strategies among other measures, was developed to respond to the need to promote breastfeeding in Colombia considering its role in children’s oral and craniofacial development. The objective of this study was to design and implement a dentistry-based educational strategy to increase the knowledge, attitudes and skills (KAS) of pregnant women and nursing mothers. The study involved four phases: 1. Application of a validated questionnaire to measure breastfeeding KAS and babies’ craniofacial development. 2. Design of an educational strategy based on the information gathered. 3. Implementation of the strategy in the same population. 4. Second application of the survey six months later to determine the impact of the strategy. In Phase 1, it was detected that of 82.9% of the women had a high level of knowledge, 85.6% had a high level of attitudes, and 50.2% of skills. Phase 2 involved the design of an educational strategy based on the findings, which highlighted the importance of breastfeeding for the newborn’s craniofacial development. In Phase 4, following strategy implementation, it was found that the KAS of the 221 women who remained in the study, increased significantly (knowledge 99.5%, attitudes 99.1% and skills 86%, p = 0.00). An important increase was also detected in terms of the concept of breastfeeding children up to two years of age, which went up from 17.6% of the mothers surveyed to 51.1%. The educational strategy developed in this study increased the knowledge, attitudes, and, especially, the skills of pregnant women and nursing mothers. It also clarified concepts that contribute to the exercise of this activity.